2020
DOI: 10.3390/nu12082462
|View full text |Cite
|
Sign up to set email alerts
|

Sinensetin Induces Autophagic Cell Death through p53-Related AMPK/mTOR Signaling in Hepatocellular Carcinoma HepG2 Cells

Abstract: Sinensetin (SIN) has been reported to exhibit anti-inflammatory and anti-cancer activity. However, the cellular and molecular mechanism by which SIN promotes hepatocellular carcinoma (HCC) cell death remains unclear. In the present study, we investigated the induction of cell death by SIN and its underlying mechanism in HepG2 cells, an HCC cell line. We found that SIN significantly induced cell death in HepG2 cells, whereas the proliferation rate of Thle2, human liver epithelial cells, was unaffected by SIN. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Autophagy has been proved to be a potential therapeutic target for OA, because it helps to alleviate the apoptosis and senescence of chondrocytes (Appleton, 2018). Previous studies have shown that Sin is an autophagy inducer used to treat colitis and hepatocellular carcinoma (Xiongjian et al, 2019;Kim et al, 2020). In our study, Sin also significantly improved the autophagy function of chondrocytes, and its protective effect on TBHP-treated chondrocytes was abrogated when autophagy was inhibited, indicating that Sin plays a protective role by enhancing autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy has been proved to be a potential therapeutic target for OA, because it helps to alleviate the apoptosis and senescence of chondrocytes (Appleton, 2018). Previous studies have shown that Sin is an autophagy inducer used to treat colitis and hepatocellular carcinoma (Xiongjian et al, 2019;Kim et al, 2020). In our study, Sin also significantly improved the autophagy function of chondrocytes, and its protective effect on TBHP-treated chondrocytes was abrogated when autophagy was inhibited, indicating that Sin plays a protective role by enhancing autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Sin is also involved in the regulation of a variety of signaling pathways, such as NF-kappaB, AKT/mTOR and MAPKs signaling (Tan et al, 2019;Li et al, 2020). A recent study showed that Sin promotes autophagy through AMPK/mTOR signaling pathway to induce hepatocellular carcinoma cell apoptosis (Kim et al, 2020). Although studies have conducted extensive studies on the function of Sin, its effect on chondrocyte autophagy and its potential therapeutic effect on the progression of OA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This assay has shown a remarkable decline in the cell viability when compared with the untreated cells. The 3a has shown an IC 50 Fundamentally, the flavonoids promote the anticancer mechanism by instigating the apoptosis and cell cycle arrest (42). The apoptosis was studies by the expression of cleaved PARP and cleaved caspase 3 (42).…”
Section: Discussionmentioning
confidence: 99%
“…The 3a has shown an IC 50 Fundamentally, the flavonoids promote the anticancer mechanism by instigating the apoptosis and cell cycle arrest (42). The apoptosis was studies by the expression of cleaved PARP and cleaved caspase 3 (42). Caspases broadly belong to the protease family that manifests specificity to aspartic acids.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study on SIN treatment in HepG2 cells, we found that SIN could induce HCC cell death in vitro (22). RNA-seq and Cuffdiff identified 43 DEGs (Table II) between SIN-untreated and SIN-treated HepG2 cells based on the selection criteria (a false discovery rate <0.05 and |log 2 FC| >1).…”
Section: Identification Of Degsmentioning
confidence: 98%